Profil Antropometri Siswa Putra Kelas VIII SMP Negeri 3 Mandrehe Kecamatan Mandrehe Kabupaten Nias Barat Tahun 2025 - Gulo, Meigesti; Munawar, Ahmad Al (Dharmas Journal of Sport, 2026)
This study aims to analyze the anthropometric conditions and nutritional status of eighth-grade students by measuring body weight, height, arm length, leg length, and calculating Body Mass Index (BMI) and body proportions. The research was conducted at a junior high school with a sample of 32 students. The results indicate that the majority of students experienced poor nutritional status, with 44% categorized as severely underweight and 44% categorized as underweight. The arm length to height ratio showed relatively short arms (0.29–0.34), while the leg length to height ratio was within normal proportions (0.46–0.55). The arm length to leg length ratio indicated an imbalance in body proportions, with arms being shorter compared to legs (0.58–0.69). These findings emphasize the need for nutritional interventions and integrated health programs to support optimal physical growth and development of students.